Heart Smart: A Virtual Self-Management Intervention for Homebound People With Heart Failure: A Pilot Study. Issue 1 (February 2023) - Frye, Sara Kate; Bell, Alison
Heart failure is a chronic medical condition that requires lifelong self-management to optimize health. Self-management strategies include self-monitoring symptoms, managing medications, modifying the diet, and maintaining healthy activity levels. However, knowledge of self-management skills is insufficient; people with heart failure must develop self-efficacy in order to take action to improve their health. Self-management programs rely on group interaction to build self-efficacy, but specialized group interventions are inaccessible to individuals who are homebound. The purpose of this pilot study was to examine the feasibility of Heart Smart, a 5-week, virtual program to increase self-efficacy for heart failure self-management. Three participants were enrolled from a large academic home health system in the greater Philadelphia area. All 3 participants demonstrated improved scores on the Self-Efficacy for Managing Chronic Diseases 6-Item Scale. Two out of the 3 participants had clinically important gains on the Kansas City Cardiomyopathy Questionnaire. All 3 participants made gains on the Atlanta Heart Failure Knowledge Test. Participants were able to log in and access the virtual meeting platform effectively with minimal training. Participant satisfaction within the group was high. These pilot study results indicate the potential for positive self-management gains, and larger scale trials of the Heart Smart intervention are recommended.